Interleukin-17A Mediates Hippocampal Damage and Aberrant Neurogenesis Contributing to Epilepsy-Associated Anxiety - Choi, In-Young; Cho, Mi-La; Cho, Kyung-Ok (Frontiers in Molecular Neuroscience, 2022)
Anxiety disorder is one of the most common comorbidities in temporal lobe epilepsy (TLE), but its neurobiological mechanisms remain unclear. Here we identified a novel target, interleukin-17A (IL-17A), which can contribute to TLE-associated anxiety. Epileptic seizures were induced in 6-week-old IL-17A wild-type (WT) and knockout (KO) mice by pilocarpine injection. To evaluate anxiety level, we subjected mice to open field and elevated plus maze (EPM) tests and measured the time animals spent in center zone or open arms. Epileptic IL-17A WT mice showed thigmotaxis and reluctance to stay in open arms, whereas IL-17A KO mice spent more time in the center area and open arms, suggesting alleviated anxiety in epilepsy. Histological assessments revealed that hippocampal neuronal death as evaluated by Fluoro-Jade B staining was significantly reduced in IL-17A KO mice. Moreover, at 6 weeks after pilocarpine-induced status epilepticus, the number of hilar ectopic granule cells was also markedly decreased by IL-17A deficiency without a difference in the proliferation of neural progenitors or the generation of newborn neurons in the dentate gyrus. Taken together, our data demonstrated that IL-17A deletion mitigates TLE-associated anxiety behavior, possibly via the hippocampal neuroprotection and the reduction of seizure-induced aberrant neurogenesis.